2012
DOI: 10.1155/2012/542727
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Augments the NMDA-Mediated TNF Suppression of MRSA-Stimulated RAW264.7 Murine Macrophages

Abstract: Background. Methicillin-resistant Staphylococcus aureus (MRSA) can stimulate massive cytokine release. Ketamine suppresses tumor necrosis factor (TNF) secretion by MRSA-stimulated RAW264.7 macrophages, and the mechanism likely involves N-methyl-D-aspartic acid (NMDA) receptor antagonism. The downstream effects of NMDA-mediated TNF suppression, specifically the PI3K/Akt and mTOR modulation, have not been described. Methods. RAW264.7 cells were stimulated for 18 hrs with 105 to 107 CFU/mL inocula of either of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…In particular RAPA was shown to be a good candidate for pharmacological modulation of dendritic cells and CD4 + CD25 + regulatory T cells . Moreover, a growing body of evidence indicates that in myeloid phagocytes (monocytes, macrophages, granulocytes and myeloid dendritic cells), the mTOR pathway is crucial for survival and activation …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular RAPA was shown to be a good candidate for pharmacological modulation of dendritic cells and CD4 + CD25 + regulatory T cells . Moreover, a growing body of evidence indicates that in myeloid phagocytes (monocytes, macrophages, granulocytes and myeloid dendritic cells), the mTOR pathway is crucial for survival and activation …”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] Moreover, a growing body of evidence indicates that in myeloid phagocytes (monocytes, macrophages, granulocytes and myeloid dendritic cells), the mTOR pathway is crucial for survival and activation. 19,[28][29][30][31] Plasticity is a hallmark of myeloid mononuclear phagocytes and in response to environmental signals these cells undergo different forms of polarized activation, the extremes of which are called classic or M1 and alternative or M2. 32,33 Although the central and pervasive action of RAPA in innate immune responses is becoming apparent, 30,34 its effect on macrophage viability or polarization is still discordant 19,31,35 or not yet studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the agonism of the NMDA receptor increases and antagonism of the same receptor diminishes the TNF response [ 6 ]. Downstream from the NMDA, the phosphoinositide-3 kinase/akt (PI3/AKT) also influences such response [ 6 , 7 ]. The next downstream signaling molecule is the mammalian target of Rapamycin (mTOR complex).…”
Section: Introductionmentioning
confidence: 99%
“…The role of mTOR as a central controller of cell growth, proliferation, and metabolism has been described but many aspects are unclear [ 8 , 9 ]. Previous studies by our group have shown that inhibition of mTOR by Rapamycin has a dose-dependent biphasic response on TNF secretion [ 7 ]. At very low doses, Rapamycin increases TNF production, but, at tenfold higher doses, TNF secretion is diminished.…”
Section: Introductionmentioning
confidence: 99%